Factors that Determine Child Behavior during Dental Treatment - Bajrić Elmedin; Kobašlija S.; Huseinbegović A.; Marković N.; Selimović-Dragaš M.; Arslanagić Muratbegović A. (Balkan Stomatological Society, 2016)
In this review paper we wanted to summarize all the aspects which could affect the behavior of the child patients in the dental office. At the beginning, the factors that are related to the child patients are mentioned. Various segments of child psychological, cognitive, physiological and other kinds of development are discussed. Also, the reasons for dental fear and anxiety (DFA) and dental behavior problems (DBP) were analyzed, and how the child dental patients could cope with them. Finally, types of patients according to their behavior in the dental office were discussed. Furthermore, the influences of child patients' parents were studied, including parenting styles, as well as factors related to dentist, dental team and the dental office. Finally, critical evaluation of administration of assets to measure the presence of DFA and DBP is provided. Every part of the text was corroborated by the results from our own and other authors' recent bibliography data.